THE DEVELOPMENT OF ANDROID-BASED LEARNING MEDIA ON THE ORGANIC COMPOUNDS - Maya Erliza Anggraeni; Abdul Hadjranul Fatah; Nopriawan Berkat Asi; Syarpin; Agtri Wulandari (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
General Chemistry is one of the compulsory subjects offered in the first year joint lectures at the Mathematics and Natural Sciences Education Department, FKIP Universitas Palangka Raya. The Covid-19 pandemic that has hit countries globally has had its own impacts and challenges for educational institutions, especially universities. Basic chemistry online lectures have combined various platforms such as google classroom, Edmodo, whatsapp groups, and online meetings such as google meet and zoom. However, this platform has some constraints, especially signal constraints, data packets, and management of shared data. Therefore, interactive learning media was developed, which can integrate text, images, audio, video and graphics, namely Android. This study aims to develop android-based general chemistry learning media on organic compound material and describe the feasibility of basic chemistry learning media. The development model used is the DDD-E model. The results of the development showed that the product resulting from the development process is an android-based learning media application in the form of an interactive e-book consisting of lesson plans, concept maps, instructions, materials, laboratory experiments, evaluation and team. Android-based learning media in the form of e-modules is suitable for use in learning Basic Chemistry. The results of the material expert's assessment obtained an average value of 82.14% (Good). The results of the media expert's assessment obtained an average value of 87.5% (Good).